Endocrine therapy or chemotherapy as first-line therapy in hormone receptor–positive HER2-negative metastatic breast cancer patients. (May 2018) - Jacquet, E.; Lardy-Cléaud, A.; Pistilli, B.; Franck, S.; Cottu, P.; Delaloge, S.; Debled, M.; Vanlemmens, L.; Leheurteur, M.; Guizard, A.V.; Laborde, L.; Uwer, L.; et al.
Abstract: Background: For hormone receptor–positive (HR+) human epidermal growth factor receptor 2 (HER2-) negative metastatic breast cancer (MBC), international guidelines recommend endocrine therapy as first-line treatment, except in case of 'visceral crisis'. In the latter case, chemotherapy is preferred. Few studies have compared these two strategies. We used the Epidemiological Strategy and Medical Economics (ESME) programme, UNICANCER, a large national observational database (NCT03275311 ), to address this question. Methods: All patients who initiated treatment for a newly diagnosed HR+ HER2-negative MBC between January 2008 and December 2014 in any of the 18 French Comprehensive Cancer Centers participating to ESME were selected. Patients should be aromatase inhibitor (AI)–sensitive (no previous AI or relapse occurring more than 1 year after last adjuvant AI). Objectives of the study were evaluation of progression-free and overall survival (OS) according to the type of first-line treatment adjusted on main prognostic factors using a propensity score. Results: Six thousand two hundred sixty-five patients were selected: 2733 (43.6%) received endocrine therapy alone, while 3532 (56.4%) received chemotherapy as first-line therapy. Among the latter, 2073 (58.7%) received maintenance endocrine therapy. Median OS was 60.78 months (95% confidence interval [CI], 57.16–64.09) and 49.64 months (95% CI, 47.31–51.64; p  < 0.0001) for patients receiving endocrine therapy alone and chemotherapy ± maintenance endocrine therapy, respectively. However, this difference was not significant after adjusting on the propensity score (hazard ratio: 0.943, 95% CI 0.863–1.030, p  = 0.19). Conclusion: In this large retrospective cohort of patients with AI-sensitive metastatic luminal BC, OS was similar, whether first-line treatment was chemotherapy or endocrine therapy. In agreement with international guidelines, endocrine therapy should be the first choice for first-line systemic treatment for MBC in the absence of visceral crisis.